DIAGNOSTIC EFFECTIVENESS OF MODERN COPROOVOSCOPIC METHODS FOR GOOSE AMIDOSTOMOSIS - Yuskiv, I.D.; Melnychuk, V.V. (Scientific Progress & Innovations, 2019)
Goose farming is one of the traditional and highly profitable livestock farming industries in Ukraine and in several countries of the world. Its successful developing and obtaining high-quality, competitive products are possible in case of available high-quality breeding poultry having high genetic potential, being well adapted to local natural- climatic conditions, as well as epizootic well-being as to invasion diseases, in par-ticular helminthiases. Pathogenic parasites, which are widely spread among domestic geese, include nema-todes of Amidostomum anseris species. Diagnostic coproovoscopic studies of waterfowl are of great im-portance in the organization of anti-parasitic measures.. In order to establish the effectiveness of modern coproovoscopic methods for goose amidostomosis, four methods were compared, namely: the bischofite method (by Dakhno I. S., 2003); the method of using carbamide (by Melnychuk V. V., 2015); the method of using sugar-salt combined solution (by Manoilo Yu. B., 2016); and the method of using a combined solution of sugar and sodium chloride (by Natiahla I. V., 2016). According to the results of the experimental studies it was revealed that the most effective method of lifetime coproovoscopic goose amidostomosis diagnostics was the method of Melnychuk V. V. with using carbamide solution, in which the percentage of positive samples ranged from 93.33 to 100.0 %, invasion intensity reached 118.67±13.50 eggs per 1 g of feces. This method ensured high accuracy of the obtained biomaterial when conducting helminth embryo microscopy. Using the method of Natiahla I. V. and Manoilo Yu. B., in which the combined mixture was used as flotation solution the number of positive samples ranged from 60.0 to 100 % and invasion intensity ranged from 37.78±4.01 to 82.67±9.73 eggs/g. The lowest diagnostic effectiveness was found while using Dakhno’s I. S. method apply-ing bischofite as flotation solution. The intensity of amidostomosis invasion, depending on the exposure, ranged from 24.44±2.94 to 66.15±11.85 eggs/g. The obtained data on the diagnostic effectiveness of coproovoscopic methods will enable to apply the most sensitive methods in the measures concerning the con-trol and prevention of goose amidostomosis.